SIKAP PEMUDA DESA TERHADAP USAHATANI SALAK ORGANIK DAN PENGARUHNYA TERHADAP MINAT BERUSAHATANI SALAK ORGANIK - Ani Dwi Wimatsari; Sunarru Samsi Hariadi; Edhi Martono (Universitas Muhammadiyah Yogyakarta, 2019)
One of the problems that occur in agricultural sector is farmer regeneration. Farmer regeneration problem does not only occur in food crop sub-sector, but also in horticulture sub-sector. One of the commodities in horticultural sub-sector which also have this problem is salak. This study aims to determine the attitude of the young generation (village youth) toward salak organic farming along with its influencing factors, and to analyze the influence of village youth attitudes towards interest of village youth to continue salak organic farming. The study was conducted in Turi District, which is the center for salak production in Sleman Regency, with a total sample of 164 village youth taken by census technique. Data were analyzed using multiple linear regression and simple regression analysis. The results showed that role of new media and the role of agricultural extensionist had negative and significant effect on the attitudes of village youth, while the perceptions of village youth on organic salak farming and the role of parents had a positive effect on village youth attitudes towards labor factors in farming. In addition, the attitude of village youth significantly affected the interest of village youth to continue organic salak farming.